2016
DOI: 10.5812/traumamon.31796
|View full text |Cite
|
Sign up to set email alerts
|

A Prospective Study of Survival After In-Hospital Cardiopulmonary Resuscitation and its Related Factors

Abstract: BackgroundDespite several studies, there is no agreement on factors that affect survival after in-hospital cardiopulmonary resuscitation (CPR).ObjectivesThis study aimed to evaluate the survival rate of in-hospital CPR and its related factors at Shahid Beheshti hospital in Kashan, Iran, in 2014.Patients and MethodsA descriptive study was conducted on all cases of CPR performed in Kashan Shahid Beheshti hospital during a 6-month period in 2014. Through a consecutive sampling method, 250 cases of CPR were studie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
26
2
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(33 citation statements)
references
References 16 publications
(24 reference statements)
2
26
2
2
Order By: Relevance
“…The survival rate was higher in morning shifts, with no patient surviving CPR in the afternoon shift. This can be owing to higher concentration and stamina of the work force in the morning (17). Likewise, there was a significant difference between the shifts in our study (P < 0.002).…”
Section: Discussionsupporting
confidence: 54%
“…The survival rate was higher in morning shifts, with no patient surviving CPR in the afternoon shift. This can be owing to higher concentration and stamina of the work force in the morning (17). Likewise, there was a significant difference between the shifts in our study (P < 0.002).…”
Section: Discussionsupporting
confidence: 54%
“…This rate was 88.6% and 63.36% in studies conducted in Iran (28,29), which indicated a satisfactory condition in the ED. Factors such as CPR duration and time of arrival of the CPR team can predict the CPR outcome (28). In spite of the insufficient trained ED physicians, it has been predicted that the rate of referral to EDs will be 2-fold by 2025 (30).…”
Section: Discussionmentioning
confidence: 64%
“…The rate of unsuccessful CPR attempts was reported to be higher than 80% in other studies (26,27). This rate was 88.6% and 63.36% in studies conducted in Iran (28,29), which indicated a satisfactory condition in the ED. Factors such as CPR duration and time of arrival of the CPR team can predict the CPR outcome (28).…”
Section: Discussionmentioning
confidence: 74%
“…The incidence of in-hospital cardiopulmonary arrest has been reported to be around 1.45 to 3.72 per thousand admissions with only 4.8% to 17% of such patients surviving till hospital discharge [15][16][17][18][19][20] . Other than failing to achieve a return of spontaneous circulation, the associated complications arising from CPR may result in significant morbidity 21 .…”
Section: Discussionmentioning
confidence: 99%